Development of Digital Comic Learning Media to Improve Conceptual Understanding of Human Respiratory System Material for Grade XI Students at SMA Negeri 3 Padangsidimpuan - Habzai, Nurul Nadhira; Amir, Almira; Nasution, Wilda Rizkiyahnur (Bioedunis Journal, 2025)
The background of this study is based on the low interest in learning and student learning outcomes in Biology material which is abstract and the limited interesting and contextual learning media. This study aims to develop learning media in the form of digital comics as an effort to improve students' conceptual understanding of the human respiratory system material in class XI of SMA Negeri 3 Padangsidimpuan. The research method used is Research and Development (RD) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The subjects of this study were students of class XI-3. The instruments used include validation questionnaires from media experts, material experts, language experts, teacher response questionnaires, student response questionnaires and conceptual understanding tests. The validation results show that the developed digital comics are categorized as very valid both in terms of content and media display with an average of 89.88%. The results of data analysis from the practicality questionnaire from teacher responses at SMA Negeri 1 Padangsidimpuan reached a percentage of 98% and the results of the student response questionnaire with a sample of 31 students reached an average value of 88.96% with a very practical category. Digital comic media, which is used to measure students' conceptual understanding of the human respiratory system material, is included in the effective category. The effectiveness of this digital comic media can be seen based on the N-Gain value of student learning outcomes, which is 56.04% with moderate criteria, and based on the results of the student effectiveness questionnaire using digital comic media, which is 87.66%. Product trials show that the use of digital comics can significantly improve students' conceptual understanding. Thus, this digital comic learning media is worthy of being used as an alternative learning media in the Biology learning process, especially in the human respiratory system material.